Testis sparing surgery in pediatric population - ŞEKERCİ, ÇAĞRI AKIN (My University, 2022)
In this review, it is aimed to illuminate the place of testicular sparing surgery in childhood testicular tumors in the light of current literature. The importance of organ-sparing surgery is highlighted because a significant portion of childhood testicular tumors are benign and organ-sparing surgery reduces morbidity without affecting disease-related survival. Testis sparing surgery can be considered as an alternative to radical inguinal orchiectomy in synchronous bilateral testicular tumors, metachronous contralateral tumors, and in the presence of normal solitary testis if preoperative testosterone level is normal and the tumor size is less than 30% of the testicular volume. However, definite recommendations could not be determined due to the lack of literature data.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Child; testicular tumor; testis sparing surgery; TERM-FOLLOW-UP; TESTICULAR-TUMORS; PARATESTICULAR TUMORS; CONSERVATIVE APPROACH; CELL TUMOR; BENIGN; MANAGEMENT; EPIDEMIOLOGY; EXPERIENCE; NEOPLASMS; Child; testicular tumor; testis sparing surgery